Sustainability calculation approach of guadua (Guadua angustifolia Kunth.) forests throughout the use of emergetic analysis - Angela Maria Arango Arango; Juan Carlos Camargo García; Juan Mauricio Castaño Rojas (Acta Agronómica)
The sustainability of guadua forests under management was assessed throughout the emergy analysis approach. The system analyzed correspond to guadua forest whose major product are culms for commercial purposes. In order to calculate the sustainability, available information on purchased inputs, renewable and nonrenewable natural resources as well as external factors, which can affect the system such as labor or inputs (ie. fuel consumption), was used for calculate indexes which describe relationship among the employed natural resources. The results showed the guadua forest system under management does not depend on external inputs and its sustainability is above 90%. In fact, the recovery ability after harvesting shown by these guadua forests is associated with a proper management, which contributes to the ecosystem conservation of functions. Considering the current management conditions, the guadua forest system is sustainable although highly dependent on natural resources. Under these conditions, the system become vulnerable since the management should be focused on guaranteeing the current conditions and therefore, their conservation.